2008
DOI: 10.1177/0192513x08322782
|View full text |Cite
|
Sign up to set email alerts
|

Parental Divorce and Sibling Relationships

Abstract: This study examines long-term effects of parental divorce on sibling relationships in adulthood and the role of predivorce parental conflict. It used large-scale retrospective data from the Netherlands that contain reports from both siblings of the sibling dyad. Results show limited effects of parental divorce on sibling contact and relationship quality in adulthood but strong effects on sibling conflict. The greater conflict among siblings from divorced families is explained by the greater parental conflict i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 49 publications
1
43
0
3
Order By: Relevance
“…The quality of adult sibling relationships may be in fl uenced by the quality of their bonds earlier in life, but as we have suggested, the longitudinal data needed to test this idea have not been collected. Suggestive of the signi fi cance of early family experience, however, one study collected retrospective data from adults about their parents' marital con fl ict and found that these recollections were related to higher levels of sibling con fl ict and poorer sibling relationship quality in adulthood (Poortman & Voorpostel, 2009 ) . Concurrent relationships in the family of origin also are important: Voorpostel and Blieszner ( 2008 ) found evidence for both consistency and compensation processes linking parent-child and sibling relationships, such that poor relationships and low contact with parents as well as high parental support were linked to sibling relationship support.…”
Section: Dimensions Of Sibling Relationshipsmentioning
confidence: 99%
See 1 more Smart Citation
“…The quality of adult sibling relationships may be in fl uenced by the quality of their bonds earlier in life, but as we have suggested, the longitudinal data needed to test this idea have not been collected. Suggestive of the signi fi cance of early family experience, however, one study collected retrospective data from adults about their parents' marital con fl ict and found that these recollections were related to higher levels of sibling con fl ict and poorer sibling relationship quality in adulthood (Poortman & Voorpostel, 2009 ) . Concurrent relationships in the family of origin also are important: Voorpostel and Blieszner ( 2008 ) found evidence for both consistency and compensation processes linking parent-child and sibling relationships, such that poor relationships and low contact with parents as well as high parental support were linked to sibling relationship support.…”
Section: Dimensions Of Sibling Relationshipsmentioning
confidence: 99%
“…The link between marital and sibling relationships is positive as evidenced by studies showing that negativity and violence in marital and sibling relationships are linked in childhood and adolescence (e.g., Brody et al, 1994 ;Dunn, Deater-Deckard, Pickering, & Golding, 1999 ;Yu & Gamble, 2008 ) , and that these associations extend to sibling relationships in young adulthood (Milevsky, 2004 ;Panish & Stricker, 2001 ) . Retrospective accounts of parents' marital con fl ict during childhood also have been linked to sibling con fl ict later in adulthood (Poortman & Voorpostel, 2009 ) . In some of this research, relationships of siblings with divorced vs. nondivorced parents have been compared, and reveal that marital con fl ict and dissatisfaction account for more variance in sibling relationships than family structure per se (Panish & Stricker, 2001 ;Poortman & Voorpostel, 2009 ) .…”
Section: Social Learning Theoriesmentioning
confidence: 99%
“…First, although some young children might actually benefit or thrive after parental divorce if they were living in a hostile environment (Amato, 2000;Riggio, 2004), most studies conclude that young children exhibit lower academic performance (Astone & McLanahan, 1991, Wolfinger et al, 2003, delayed psychological development (Kurdek et al, 1994), strained relationships with family members (Poortman, 2009), and poorer mental health (Ängarne-Lindberg, 2009). These consequences, especially those that have the potential to persist into the later stages of the child's life course, could be initially affected through short-term disruptions in education (Amato 2000;Booth & Amato, 1991) and social networks (Cotton, 1999;Kim & Woo, 2011).For example, when experiencing parental divorce at a young age, the custody arrangements agreed on by the parents might disrupt a child's social network and education (e.g., by moving between parent's houses), thereby decreasing later educational attainment (Wolfinger et al, 2003), which often leads to poor occupational outcomes.…”
Section: Effects Of Parental Divorcementioning
confidence: 99%
“…As evidence of this pathway, children whose social networks were disrupted by parental divorce had a lower sense of control (Kim & Woo, 2011) and thus were less motivated to attain a higher level of education and then acquire a good job. The immediate disruption caused by parental divorce and the subsequent trajectories set off by those disruptions have the potential to affect a child's social and familial relationships, as well as overall mental health throughout the life course (Poortman, 2009).…”
Section: Effects Of Parental Divorcementioning
confidence: 99%
“…Simply knowing a child's living arrangements tells us little about the family environment in which they reside and comparing outcomes of children in intact and single-parent homes neglects the complexities of family life (Videon, 2002). It has been argued that the parental conflict associated with divorce rather than divorce per se may cause children to be worse off (Poortman & Voorpostel, 2009). Indeed when marital conflict is intense, separation removes children from this high conflict environment, improving their well-being (Morrison & Coiro, 1999).…”
Section: Introductionmentioning
confidence: 99%